The integral role of lifestyle in the prevention and management of hypertension and associated cardiometabolic and cognitive disorders: a review - Wang, Qian; Wu, Dan; Huang, Yan (Frontiers in Endocrinology, 2025)
Hypertension represents a paramount global health challenge, intricately linked to cardiovascular, metabolic, and cognitive morbidity. This narrative review provides a critical synthesis of current evidence, anchored by a systematic literature search, to delineate the integral role of comprehensive lifestyle interventions in the prevention and management of hypertension and its complications. Our analysis demonstrates that evidence-based, multidimensional strategies—including dietary modifications (e.g., DASH and Mediterranean diets), regular physical activity, structured weight management, and stress reduction—effectively lower blood pressure, improve metabolic parameters, and attenuate target organ damage. These non-pharmacological approaches act synergistically with antihypertensive drug therapy and can be personalized through digital health technologies. The findings underscore that embedding structured lifestyle medicine into clinical practice and public health policy is an indispensable, cost-effective strategy for alleviating the global burden of hypertension.